The Effect of Halal Awareness and Lifestyle on The Purchase Decision of Japanese Food in Jakarta - Alifah Nurfajrina; Tati Handayani; Lili Puspita Sari (Universitas Mercu Buana, 2021)
This study uses independent variables, namely halal awareness and lifestyle to know and analyze the influence of these two variables on Muslim consumers' purchasing decisions on Japanese food in Jakarta. This research study uses quantitative methods. The source of the population taken by the researcher comes from Muslim consumers who have visited or have purchased food products from Japanese restaurants in Jakarta. For the number of samples in this study using as many as 150 respondents from consumers of Yoshinoya, Pepper Lunch, and Ramen Seirock-Ya restaurants in the Jakarta area. The data collection instrument studied was obtained by distributing questionnaires. To determine the magnitude of the influence of variables in this study, the analytical technique used is multiple linear analysis. SPSS (Statistics Package for Social science) software version 20 is the tool used to process this study. The results of the tests carried out showed that the variables of halal awareness and lifestyle had a positive and significant effect partially and jointly on the purchasing decisions of Muslim consumers on Japanese food in Jakarta.